Modeling and formal analysis of urban road traffic - Avram, Camelia (2013)
Modern life in cities leads to complex urban traffic road and, sometimes, to go from one point to another, in a city, is a hard and very complex task. The use of assisted systems for helping drivers on their task of reaching the desired destination is being common, mainly systems like GPS location systems or other similar systems. The main gap of those systems is that they are not able to assist drivers when some unexpected changes occur, like accidents, or another unexpected situations. In this context, it would be desirable to have a dynamic system to inform the drivers, about everything that is happening "online". This work is inserted in this context and the work presented here is one part of a bigger project that has, as main goal, to be a dynamic system for assisting drivers under hard conditions of urban road traffic. In this paper is modeled, and formally analyzed, the intersection of four street segments, in order to take some considerations about this subject. This paper presents the model of the considered system, using timed automata formalism. The validation and verification of the road traffic model it is realized using UPPAAL model-checker.